History-Based Islamic Education Management at Madrasah Aliyah Private Islamic Boarding School Mawaridussalam, Batang District Quiz. (Learning Planning Study) - Muhammad Sapii Harahap; Wahyudin Nur Nasution; Neliwati Neliwati; Nunzairina Nunzairina (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to find out the history and planning of learning in improving teacher performance at Madrasah Aliyah Modern Islamic Boarding School, Batang Quiz District.As for the research method used, this type of research is qualitative research, namely field research, with the aim of explaining the phenomenon as deeply as possible through collecting data as deeply as possible. Methods of data collection techniques by way of observation, interviews and document studies, data sources, data analysis and scrutinizing the validity of the data refers to qualitative research.The final results of this study indicate that 1) Madrasah Aliyah Pondok Pesantren Modern Mawaridussalam is a Madrasa that has only been established since 2008, around 14 years old. From 2010 to 2022 the Head of Madrasah Aliyah Aliyah Private Mawaridussalam has been occupied by two people, namely: 1) Nurrokhman, SH., MM, period 2010-2015, and 2) Arief Persada Lift, S.Pd.I., MM, period 2016 – present. 2) Planning of learning activities in improving teacher performance in the Deli Serdang district Private Madrasah Aliyah, namely the Mawaridussalam Private Madrasah Aliyah is carried out by involving teachers to compile all of these programs, while the planning programs are, a) Learning implementation plans, b) Plans for learning approaches and methods , c) Planning for learning tools or media, d) Planning for learning evaluation, e) Planning for preparing a Learning Implementation Plan (RPP), f) Planning for hiring teachers/teachers, and g) Planning for teacher development.